ANALYSIS OF SEA FISH CONSUMER BEHAVIOR IN TRADITIONAL MARKETS ARENGKA CITY OF PEKANBARU RIAU PROVINCE - Nuri Resty Ani; Kusai '; Zulkarnain ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Consumer behavior is learned to know how the behavior and attitude of consumers in buying a product. This research use survey method, interview and field observation then data measured using likert scale. The analysis of this research use correlation to find the relation of characteristic to consumer behavior. Characteristics taken include age (X1), education (X2), income (X3) and number of family members (X4) while consumer behavior such as many purchases of marine fish in one month (Y1), number of deep-sea fish purchases (Y2) and Consumer preference (Y3). The result shows there is a real relationship between the characteristics of consumer behavior such as education (X2) related to the preference (Y3) with a significant level of (0.001), Income (X3) correlates with the preference (Y3) significant level (0.03), the number of family members (X4) is related to many significant purchases (Y1) (0.004) And the number of family members (X4) corresponds to the number of once purchases (Y2) with significant levels (0.004).Keywords: consumer behavior, marine fish, traditional market of arengka.